Microbiologic characterization and antimicrobial susceptibility of Clostridium tetani isolated from wounds of patients with clinically diagnosed tetanus. - Campbell, J; Lam, T; Huynh, T; To, S; Tran, T; Nguyen, V; Le, T; Nguyen, V; Parry, C; Farrar, J; Tran, T; Baker, S (2009)
Clostridium tetani is the etiologic agent of the muscle-spasming disease tetanus. Despite an effective vaccine, tetanus is an ongoing problem in some developing countries. Diagnosis by bacterial culture is not done because it is generally unnecessary and the entry of route of the bacteria can be inapparent. We attempted to isolate and evaluate C. tetani from the wounds of 84 patients with tetanus. We effectively isolated C. tetani from 45 patients. All strains tested positive by polymerase chain reaction for the gene encoding tetanus neurotoxin. Antimicrobial susceptibilities were determined by disc diffusion and E-test. All C. tetani isolates were susceptible to penicillin and metronidazole but resistant to co-trimoxazole. Despite treatment with high doses of penicillin, C. tetani was isolated after 16 days of intravenous penicillin in two cases. These data show that the intravenous route for penicillin may be inadequate for clearing the infection and emphasizes wound debridement in the treatment of tetanus.